2021
DOI: 10.1029/2020gl091266
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Nitrous Oxide Emissions in the U.S. Midwest: A Top‐Down Study Using High Resolution Airborne In‐Situ Observations

Abstract: The densely farmed U.S. Midwest is a prominent source of nitrous oxide (N2O) but top‐down and bottom‐up N2O emission estimates differ significantly. We quantify Midwest N2O emissions by combining observations from the Atmospheric Carbon and Transport‐America campaign with model simulations to scale the Emissions Database for Global Atmospheric Research (EDGAR). In October 2017, we scaled agricultural EDGAR v4.3.2 and v5.0 emissions by factors of 6.3 and 3.5, respectively, resulting in 0.42 nmol m−2 s−1 Midwest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Although top-down and bottom-up estimates of global N 2 O emissions are consistent ( 3 ), uncertainty increases, and methods often diverge at smaller spatial scales and when emissions are partitioned into different source categories. For example, N 2 O emissions estimated using top-down measurements were higher than those based on bottom-up approaches for the US Corn Belt ( 4 , 5 ), an important agricultural region characterized by intensive cropping with substantial N inputs. In contrast, a study in Europe found that N 2 O emissions inferred from inversions were consistent with those reported in national inventories based on bottom-up methods ( 6 ).…”
mentioning
confidence: 95%
“…Although top-down and bottom-up estimates of global N 2 O emissions are consistent ( 3 ), uncertainty increases, and methods often diverge at smaller spatial scales and when emissions are partitioned into different source categories. For example, N 2 O emissions estimated using top-down measurements were higher than those based on bottom-up approaches for the US Corn Belt ( 4 , 5 ), an important agricultural region characterized by intensive cropping with substantial N inputs. In contrast, a study in Europe found that N 2 O emissions inferred from inversions were consistent with those reported in national inventories based on bottom-up methods ( 6 ).…”
mentioning
confidence: 95%
“…Two exceptionally high excursions from background in atmospheric N 2 O of 12 and 22 ppb were observed in NOAA data at West Branch, Iowa. In addition, excursions of 11 ppb or higher were observed over Iowa in four low altitude flask samples collected by the ACT‐America aircraft campaign (Davis et al., 2018; Eckl et al., 2021; Wei et al., 2021). The corresponding STILT‐WRF influence footprints extended across Iowa and parts of Nebraska, South Dakota, and Wisconsin (Figure S1 in Supporting Information S1), leading to a large late‐February emission pulse in the inversion results across much of the Midwest (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…These campaigns typically are confined to a restricted time frame, for example, 1–2 months, often in summer. Thus, if the aircraft campaigns coincide with the peak enhancements in atmospheric N 2 O in May or June, they may infer large fluxes and conclude that the inventories significantly underestimate N 2 O emissions and/or have inappropriate seasonality (Eckl et al., 2021; Kort et al., 2008; Miller et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Instead ABL mole fractions outside of the influence of the region of interest are matched with simulations of both background mole fractions and fluxes from outside the region of interest to isolate mole fraction enhancements from the region of interest (Barkley et al 2017). This approach is difficult to apply to biogenic CO 2 fluxes, since they are so broadly distributed, but this method works well for studying emissions from discrete source regions such as cities or anthropogenic CH 4 emissions (Barkley et al 2019a(Barkley et al , 2021 and agricultural N 2 O emissions (Eckl et al 2021).…”
Section: Analysesmentioning
confidence: 99%